Analysis Of Cultural Attractions, Digital Information, And Social Media Content On Tourist Satisfaction At Maimun Palace, Medan - Dewi Apriliya Ritonga; Hidayati Purnama Lubis; Fitra Arlina Nasution (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of cultural attractions, digital information, and social media content on tourist satisfaction at Maimun Palace in Medan. The research employed an associative quantitative approach involving 99 domestic tourists who visited Maimun Palace. The respondents were selected using an accidental sampling technique. Data were analyzed using multiple linear regression with the assistance of SPSS software.The results indicate that cultural attractions have a positive and significant effect on tourist satisfaction. Meanwhile, digital information and social media content do not show a significant partial effect on tourist satisfaction. However, simultaneously, these three variables have a positive and significant influence on tourist satisfaction. The coefficient of determination (R²) value of 0.500 indicates that 50% of the variation in tourist satisfaction can be explained by cultural attractions, digital information, and social media content, while the remaining 50% is influenced by other factors outside the research model. Overall, the findings highlight that cultural values and local heritage remain essential factors in shaping tourist satisfaction in historical tourism destinations such as Maimun Palace. Therefore, destination managers are encouraged to optimize cultural potential through more creative, informative, and relevant digital promotional strategies.